Analysis of Employees’ Profiles of Responses to Personal and Workplace-Related Factors of Psychological Capital: The Profile Analysis via Multidimensional Scaling Approach - Lily Chernyak-Hai; Tomer Schmidt-Barad; Se-Kang Kim (Journal of Work and Organizational Psychology)

(untitled)
Previous studies have highlighted psychological capital (PsyCap) as crucial for well-being, linking it to many positive workplace outcomes. Just as recognizing individual psychological or physical profiles helps tailor specific educational or treatment interventions, and personality or demographics assessments guide workplace decisions and behavior, understanding employees' psychological profiles related to their well-being can be highly valuable. This study goes beyond typical statistical analyses, using profile analysis via multidimensional scaling (PAMS) to explore employees' PsyCap profiles in relation to personal sense of power, trait self-control, perceived conflict, leader-member exchange, perceived organizational support, and organizational politics. The results reveal two central core profiles, showing that employees experiencing high organizational politics, intragroup conflict, reduced organizational support, and lower quality leader-member exchange, report lower PsyCap. These findings have methodological and practical implications, enhancing the understanding of PsyCap in workplaces and offering insights for managers and HR professionals..